THEORETICAL AND METHODOLOGICAL FUNDAMENTALS OF PSYCHOLOGICAL STABILITY PROBLEMATICS OF THE ARMED FORCES OF UKRAINE PERSONNEL CONDITIONED BY THE RUSSIAN FEDERATION ARMED AGGRESSION - Кравченко, К. (Київський національний університет імені Тараса Шевченка, 2022)
The subject of this article is framed by the current threats and challenges, namely the conduct of hostilities in eastern Ukraine and disappointing predictions about the potential start of a full-scale offensive of Russian troops on our country. In such circumstances, it can be argued that the issue of psychological stability of the Armed Forces of Ukraine is important, relevant and urgent in its solution. It should be noted that the psychological resilience of the personnel of the Armed Forces of Ukraine (and other law enforcement agencies) is one of the important factors in the reliability and effectiveness of activities during hostilities and the impact of other various hybrid threats. The purpose of the article is to analyze the scientific developments, their generalization and substantiation of the necessary recommendations for improving the existing system of formation, provision and restoration of psychological stability of the personnel of the Armed Forces of Ukraine. Considering the issue of psychological stability of the Armed Forces of Ukraine, the authors of the article set themselves the following tasks: 1) to summarize the views of domestic and foreign researchers on psychological stability as a subject of research; 2) to determine the set of stress factors in relation to which it is necessary to form the psychological stability of the personnel of the Armed Forces of Ukraine; 3) consider the structure of psychological stability; 4) to analyze the features of the formation of psychological stability; 5) propose methods for assessing psychological resilience; 6) provide methodological recommendations for the formation and maintenance of psychological stability in modern hybrid threats.

Тематику зумовлено сучасними загрозами та викликами сьогодення, а саме: веденням бойових дій на сході України, невтішними прогнозами щодо потенційно можливого та реальним початком повномасштабного наступу військ РФ на нашу державу. Стверджено, що питання психологічної стійкості особового складу ЗСУ важливе, актуальне та невідкладне у своєму вирішенні. Зазначено, що психологічна стійкість особового складу ЗСУ (та інших силових структур) виступає одним із важливих чинників надійності та ефективної діяльності під час ведення бойових дій та впливу інших різноманітних гібридних загроз. Проаналізовано наукові напрацювання, їхнє узагальнення та обґрунтування необхідних рекомендацій щодо вдосконалення існуючої системи формування, забезпечення та відновлення психологічної стійкості особового складу ЗСУ. Розглянуто таку проблематику психологічної стійкості особового складу ЗСУ та задачі: 1) узагальнити погляди вітчизняних і зарубіжних дослідників щодо психологічної стійкості як предмета наукових досліджень; 2) визначити сукупність стрес-факторів, стосовно яких необхідно формувати психологічну стійкість особового складу ЗСУ; 3) розглянути структуру психологічної стійкості; 4) проаналізувати особливості формування психологічної стійкості; 5) запропонувати методи оцінки психологічної стійкості; 6) надати методичні рекомендації щодо формування та підтримки психологічної стійкості в умовах сучасних гібридних загроз.
ТЕОРЕТИКО-МЕТОДОЛОГІЧНІ ЗАСАДИ ПРОБЛЕМАТИКИ ПСИХОЛОГІЧНОЇ СТІЙКОСТІ ОСОБОВОГО СКЛАДУ ЗБРОЙНИХ СИЛ УКРАЇНИ В УМОВАХ ЗБРОЙНОЇ АГРЕСІЇ РОСІЙСЬКОЇ ФЕДЕРАЦІЇ
Keywords: psychological resilience; personnel of the Armed Forces of Ukraine; combat stress; structure of psychological resilience; formation of psychological resilience; assessment of psychological resilience; психологічна стійкість; особовий склад Збройних Сил України; бойовий стрес; структура психологічної стійкості; формування психологічної стійкості; оцінка психологічної стійкості